Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1037/com0000089
|View full text |Cite
|
Sign up to set email alerts
|

Common marmoset (Callithrix jacchus) personality.

Abstract: Increasing evidence suggests that personality structure differs between species, but the evolutionary reasons for this variation are not fully understood. We built on earlier research on New World monkeys to further elucidate the evolution of personality structure in primates. We therefore examined personality in 100 family-reared adult common marmosets (Callithrix jacchus) from three colonies on a 60-item questionnaire. Principal components analyses revealed five domains that were largely similar to those fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
111
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(129 citation statements)
references
References 87 publications
12
111
6
Order By: Relevance
“…Consistent with past research (Inoue‐Murayama et al., ; Iwanicki & Lehmann, ; Koski & Burkart, ; Koski et al., ; Šlipogor et al., ), we found moderate to large reaction norm intercept repeatability (Rnormalintercepttrue~ range: 0.33–0.91; see Figure a), providing evidence for personality across observational periods. As expected given our short focal sampling duration and observational methodology, which generally produce high observation–level variance (Martin & Suarez, ), long‐term (Rnormallongtermtrue~ range: 0.04–0.31) and short‐term (Rnormalshortermtrue~ range: 0.06–0.38) repeatability estimates were low to moderate.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with past research (Inoue‐Murayama et al., ; Iwanicki & Lehmann, ; Koski & Burkart, ; Koski et al., ; Šlipogor et al., ), we found moderate to large reaction norm intercept repeatability (Rnormalintercepttrue~ range: 0.33–0.91; see Figure a), providing evidence for personality across observational periods. As expected given our short focal sampling duration and observational methodology, which generally produce high observation–level variance (Martin & Suarez, ), long‐term (Rnormallongtermtrue~ range: 0.04–0.31) and short‐term (Rnormalshortermtrue~ range: 0.06–0.38) repeatability estimates were low to moderate.…”
Section: Resultssupporting
confidence: 91%
“…The sociability and arousal clusters discovered here are well supported by and consistent with past marmoset personality research. In particular, the sociability cluster is consistent with the behavioural functions of the "Sociability" (Inoue-Murayama et al, 2018) and "Agreeableness" syndromes (Iwanicki & Lehmann, 2015;Koski et al, 2017) previously described with rating methods, while the arousal cluster is consistent with "Inquisitiveness" (Koski et al, 2017), "Openness" (Iwanicki & Lehmann, 2015), and the locomotor component of "Stress-Activity" (Šlipogor et al, 2016).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…A second set of behaviours defining cotton-top tamarin Extraversion included indices related to individuals' tendencies to explore their environment. In this way, tamarin Extraversion partly resembled common marmoset Inquisitiveness (Koski et al, 2017) and Openness dimensions (Iwanicki and Lehmann, 2015) identified by questionnaires (for details see Table S19), and…”
Section: Cotton-top Tamarin Personality Modelmentioning
confidence: 72%
“…Confidence included dominance-related behaviours, low levels of scratching and indices connected to using the space and resources. Tamarin Confidence corresponded to the Assertiveness dimension in one ratings-based study of common marmosets (Koski et al, 2017).…”
Section: Cotton-top Tamarin Personality Modelmentioning
confidence: 92%